2018
DOI: 10.1007/s00526-017-1289-3
|View full text |Cite
|
Sign up to set email alerts
|

Discrete minimisers are close to continuum minimisers for the interaction energy

Abstract: Abstract. Under suitable technical conditions we show that minimisers of the discrete interaction energy for attractive-repulsive potentials converge to minimisers of the corresponding continuum energy as the number of particles goes to infinity. We prove that the discrete interaction energy Γ-converges in the narrow topology to the continuum interaction energy. As an important part of the proof we study support and regularity properties of discrete minimisers: we show that continuum minimisers belong to suita… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 79 publications
0
6
0
Order By: Relevance
“…The remaining set of model coefficients is somehow more technical. In this respect, for the sake of simplicity, we have further assumed that (i) V adh ¼ 2v adh , consistently with [16]; (ii) v t i (t)t j (t) adh =v rep , 5d 3 c =4d 3 a (in particular, we have fixed v adh =v rep ¼ 0:005 and V adh =v rep ¼ 0:01) so that the interactions laws result H-stable, see recent works in [24,29,30] and references therein; and (iii) a sdf 7 ¼ 10a sdf 4 with a sdf 4 [ (0, 0:1] and a sdf 7 [ (0, 1], according to [13]. For the estimate of the remaining parameters, i.e.…”
Section: Numerical Resultsmentioning
confidence: 99%
“…The remaining set of model coefficients is somehow more technical. In this respect, for the sake of simplicity, we have further assumed that (i) V adh ¼ 2v adh , consistently with [16]; (ii) v t i (t)t j (t) adh =v rep , 5d 3 c =4d 3 a (in particular, we have fixed v adh =v rep ¼ 0:005 and V adh =v rep ¼ 0:01) so that the interactions laws result H-stable, see recent works in [24,29,30] and references therein; and (iii) a sdf 7 ¼ 10a sdf 4 with a sdf 4 [ (0, 0:1] and a sdf 7 [ (0, 1], according to [13]. For the estimate of the remaining parameters, i.e.…”
Section: Numerical Resultsmentioning
confidence: 99%
“…While explicit analytical explorations are often difficult in agent-based models, we remark on two areas that could benefit from further mathematical exploration. First, we have built on recent investigations on the H-stability properties of adhesive/repulsive pairwise interaction potentials (Cañizo et al 2015;Cañizo and Patacchini 2018;Carrillo et al 2018;Ruelle 1969), that have allowed us to identify parameter regimes under which the model system evolves to a physically realistic configuration. Such analytical studies have in fact offered us welcome constraints for streamlining the tricky process of parametrisation.…”
Section: Discussionmentioning
confidence: 99%
“…In this respect, it has been shown that the large-time behaviour of particle systems subjected to non-local pairwise interactions is related to the H-stability of the relative kernels and potentials, see Ruelle (1969). In particular, taking advantage of the characterization of H-stable potentials provided in Ruelle (1969), recent works (such as Cañizo et al 2015;Cañizo and Patacchini 2018;Carrillo et al 2018) provide a criterion that determines a subregion of the parameter space of the repulsive-adhesive interacting kernels that results in realistic crystalline cell pattern. Accounting for these analytical results, for any pair αβ ∈ {N N, N P, P N , P P}, the parameters F r and F αβ a must satisfy the relation…”
Section: Parameters Related To Cell Resistance To Compression and Celmentioning
confidence: 99%
See 1 more Smart Citation
“…By the fattening instability condition from [5], one should be able to arrange As seen in [11] for the particle system, as the repulsive power crosses the threshold of stability for a single spherical shell, particles begin to align themselves on multiple spheres. Approaches such as those in [27,17] using Γ-convergence of interaction energy functionals may ultimately bridge the gap.…”
Section: Ode System For Convexmentioning
confidence: 99%